2020
DOI: 10.1109/access.2020.3031762
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Multi-Modal Deep Learning using Collaborative Concat Layer in Health Bigdata

Abstract: A health model based on data has various missing values depending on the user situation, and the accuracy of a health model requiring variables that the user cannot collect appears low. A deep learning health model is fitted by learning weights to increase accuracy. This implies that additional learning is required when the environment changes, such as when new variables are added or deleted depending on the user situation. In the process of applying a deep-learning-based health model to the user situation, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To achieve effective tracking of targets, it is necessary to establish the target's movement mode reasonably and select appropriate filtering and tracking methods. In the case of manoeuvring target QINGWEN LONG, WENJIN HE, LING YIN, WENXING WU movements, it is difficult to be precise with an accurate numerical model due to the lack of sufficient a priori [18]. Therefore, there are only a few more accurate movement models for simulation under different conditions.…”
Section: Construction Of a Mathematical Model Of A Moving Target Base...mentioning
confidence: 99%
“…To achieve effective tracking of targets, it is necessary to establish the target's movement mode reasonably and select appropriate filtering and tracking methods. In the case of manoeuvring target QINGWEN LONG, WENJIN HE, LING YIN, WENXING WU movements, it is difficult to be precise with an accurate numerical model due to the lack of sufficient a priori [18]. Therefore, there are only a few more accurate movement models for simulation under different conditions.…”
Section: Construction Of a Mathematical Model Of A Moving Target Base...mentioning
confidence: 99%
“…Another thrilling revelation is that most studies [70,77,79,84,94,97,106,108,[116][117][118][119][120][121] used Deep Neural Networks (DNN), such as LSTM and Convolutional Neural Network (CNN), as shown in Fig. 6.…”
Section: Big Data Platforms Tool In Bdamentioning
confidence: 99%
“…ML algorithm's hybridisation is an excellent technique to compensate for the weakness in the individual algorithm [9] . However, it was revealed that few studies out of 66 papers reviewed adopted it [70,83,85,88,101,102,107,108,118,122] . From Fig.…”
Section: Big Data Platforms Tool In Bdamentioning
confidence: 99%
“…The second CNN structure uses three structures similar to the model described above. The structures are connected by concatenate layer [63] and work together simulta neously processing PRI, PD parameters and TW to determine the class of input signals The last layer of this structure is the dense type and makes final recognition of the signa (Figure 8 and Table 4). The model described here is depicted in more detail in Figure 8.…”
Section: Layer Numbermentioning
confidence: 99%